A Rare Cause of Acute Kidney Injury: Primary Renal Lymphoma in a Patient with Human Immunodeficiency Virus - Ruslinda Mustafar; Lydia Kamaruzaman; Beh Hui Chien; Azyani Yahaya; Noor’Ain Mohd Nasir; Rozita Mohd; Rizna Cader; Kong Wei Yen (Case Reports in Medicine)
We reported a case of primary renal lymphoma (PRL) presented with non-oliguric acute kidney injury and bilateral kidney infiltrates in an individual with human immunodeficiency virus (HIV) disease. Acute kidney injury secondary to lymphoma infiltrates is very rare (less than 1% of hematological malignancy). A 37-year-old gentleman with underlying human immunodeficiency virus (HIV) disease was on combined antiretroviral therapy since diagnosis. He presented to our center with uremic symptoms and gross hematuria. Clinically, bilateral kidneys massively enlarged and were ballotable. Blood investigations showed hemoglobin of 3.7 g/L, urea of 65.6 mmol/L, and serum creatinine of 1630 µmol/L with hyperkalemia and metabolic acidosis. An urgent hemodialysis was initiated, and he was dependent on regular hemodialysis subsequently. Computed tomography renal scan showed diffuse nonenhancing hypodense lesion in both renal parenchyma. Diagnosis of diffuse large B cell lymphoma with germinal center type, CD20 positive, and proliferative index 95% was confirmed via renal biopsy, and there was no bone marrow infiltrates. Unfortunately, the patient succumbs prior to initiation of chemotherapy.